YORUBA FILM INDUSTRY AND ITS (AUTO) – BIOGRAPHICAL GENRE - Azeez Akinwumi Sesan (Institut Seni Indonesia Yogyakarta, 2026)
The quantity of films produced in Yoruba film industry over the years reveals different genres such as love and romance, thriller, history and [auto] biography which is later described as biopic in this article. A consideration of the trends in the making of biopic reveals that it evolves from Alarinjo theatrical tradition through the adopt stage to the adept stage of film production. The adopt stage is a phase of experimentation as seen in the production of biopic films in the video film mode while the adept stage is a phase of professionalism as found in the technological innovations in the production of biopic films in cinematic mode and on streaming platforms. With the qualitative approach of literature review, this article identifies that [auto] biographical genre of Yoruba film industry can be described as biophoty or biopic owing to the fact that most of these films discuss individual experiences within the [mis] fortunes of their respective communities. A comparative analyses of Adebayo Faleti’s Bashorun Gaa and Austen-Peters’ House Gaa reveal an influence of intentionality and functionalism in the production of Yoruba biopic films. There is, however, a need for the film makers to strike a balance between the pedagogy and artistry of their texts as well as between the economic interests and historical value of their products.